Timing of lactated Ringer’s administration relative to Sepsis-3 diagnosis and 28-day mortality: A retrospective propensity score-matched cohort study - Yujie Huang; Jiayue Zou (Sage Open Medicine, 2026)
Background Balanced crystalloids are preferentially recommended over saline for sepsis resuscitation; however, the optimal timing of administration remains to be defined. Methods This retrospective cohort study utilized the Medical Information Mart for Intensive Care IV (MIMIC-IV) database to analyze adult patients meeting Sepsis-3 criteria. Patients were stratified by Lactated Ringer’s (LR) administration timing relative to documented Sepsis-3 onset: Group A (LR initiation ≤24 h after onset), Group B (LR initiation ≤24 h before onset), Group C (LR initiation 24-48 h after onset), and Group D (reference: no LR exposure during intensive care unit [ICU] admission). The primary outcome was 28-day all-cause mortality. To address confounding, Group B patients were 1:1 Propensity-Score Matched (PSM) with Group D counterparts, followed by multivariable Cox regression and sensitivity analyses. Results PSM generated a balanced cohort of 3,876 patients (1,938 in Group B vs. 1,938 untreated Group D counterparts). Multivariable Cox regression analysis showed that pre-onset LR exposure remained associated with lower 28-day mortality after adjustment for clinical covariates. In additional post-PSM sensitivity analyses, this association persisted after further adjustment for elective surgery and total recorded fluid volume during the 24 hours preceding Sepsis-3 onset. To address timing-related bias, we also compared the ICU admission-to-SOFA time interval and performed a 24-hour ICU-admission landmark analysis; the association remained in the landmark cohort. Kidney outcomes were mixed: any acute kidney injury (AKI) was more frequent in Group B, whereas Kidney Disease: Improving Global Outcomes (KDIGO) stage 3 AKI and renal replacement therapy were less frequent. Conclusion Pre-diagnosis LR exposure within 24 hours before Sepsis-3 onset was associated with lower 28-day mortality in adult patients with sepsis. These observational findings are hypothesis-generating and should not be interpreted as evidence supporting prophylactic LR administration before Sepsis-3 onset.